Rehabilitation system of human micromotor capabilities: concept and design. Issue 2 (1st December 2022) - Berro, S M; Timofeev, A N
Abstract: Nowadays many modern prostheses hand are available on the market today, but they are still far from being able to completely replace the human hand. In addition, there are many factors that limit the ability to fully use the prostheses by individuals with hand disability caused by amputation or nerve damage. This article presents a new concept of hand disability rehabilitation means, which allows precise manipulation of the instrument and, thus, a system to facilitate the reintegration in the labour market. The operation of tool manipulation is divided into initial rough and final fine movement phases. At the initial phase, the prosthesis is freely transferred in the workspace of the user stump. the precise movement of the instrument at the final phase is performed by a micromanipulator built into the prosthesis and resting on a table or other environmental objects. An inverted system is possible, in which the manipulator is installed on the desktop, where then the prosthesis can rest or the targeted object is fixed on it, for example, assembly process. The manipulator is controlled either by the prosthesis socket or by an external device. In the latter case, the user carries out the control actions by various parts of the body or by voice. As an example of a possible implementation of this concept, the design of a prosthesis with an integrated three-degree manipulator carried on adaptive support is described. The support naturally adjusts to the comfortable height and orientation of the tool, then its braked. A computer model of speed-position control of the rehabilitation system is presented.